PRARANCANGAN PABRIK EXPANDED POLYSTYRENE DENGAN POLIMERISASI SUSPENSI DENGAN KAPASITAS 40.000 TON/TAHUN - , RENI MARLINA; , Prof. Ir. Rochmadi, SU., Ph.D ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The process of expanded polystyene production consists of two main steps, the polymerization of styrene and impregnation of polystyene with pentane. Polymerization of styrene takes place in a stirred tank reactor with semi batch process at constant temperature (90oC) and pressure 1 atm. Impregnation of polystyene with pentane is carried out in a batch reactor at temperature 90oC and pressure 7 atm. The expanded polystyrene plant with the capacity of 40,000 tonnes/year will be built in Cilegon, Banten, which is considered as raw material oriented plant. The plant needs area 5 hectares and 165 employees. Plant location is close to the sea, so that water for plant utility unit utilizes seawater. The expanded polystyene production requires styrene 46802,8 tonnes/year, polyvinyl alcohol 219,1 tonnes/year, pentane 13641,4 tonnes/year, and benzoyl peroxide 6,9 tonnes/year. The required utilities are process water 227.364 tonnes/year, cooling water 1.703.476,6620 tonnes/year, steam 444.040,8345 tonnes/year, fuel oil 26.117,0655 and 792.000 m3/year of instrument air. Based on economic analysis with the price of monomer styrene $1,000/ton and expanded polystyene product $1,800/ton, the expanded polystyene plant has fixed capital $ 6,975,913.05 + Rp 106.903.419.500,00 and working capital $ 12,293,571.35 + Rp 3.131.917.300,00. At 100% production rate, obtained ROI before tax of 34,64 %, ROI after tax of 17,32 %, POT before tax of 2,24 years, POT after tax of 3,66 years, with BEP at 40,10%, SDP at 24,26 %, and 36,70 % for DCFRR. Based on consideration of the economic evaluation results, this expanded polystyene plant with capacity 40.000 tonnes / year is worth to be studied further